CNC LASER AS A WAY TO IMPLEMENT ADAPTIVE TECHNOLOGY - Aleksiienko, Hordii (Global Prosperity, 2022)
The article reveals the principles of using a laser in CNC as a way to implement adaptive technology. The mechanism of the introduction of modern adaptive technology on an industrial scale is described. The concept of the coordinate measuring machine as the most important general-purpose device for control of details of a difficult form in the industry is structured. It is emphasized that for the measurement of large complex parts, methods are used that are able to register the coordinates of a point with a range of measurements of several meters; the most common methods are laser interferometry, photogrammetry and laser radar. Each of the above methods describes in detail and substantiates the most relevant area of their application. A CNC laser system has been formed, which is able to measure the position of a complex workpiece shape, its dimensions and angle of rotation. The structure of the laser system is schematically shown, and the principle of operation is described. The general structure of the CNC system for laser processing control is offered, the feature of which is universality and the possibility to create control systems for different tasks on the basis of the general basic model. It is emphasized that the list of commands created by the interpreter when processing the control program is available to both the interpolator and the external control module, which provides both direct drive control and scanner control within a single control program. It is noted that in order to ensure the correct order of issuance of control signals to the drives, as well as to implement the possibility of direct control of both modules, the output added a ring buffer with structures containing information about both control and current status data for indication terminals. Each structure in the buffer has a timestamp, which allows some programs of this architecture to do without real-time mode for the interpolator. It is emphasized that the implementation of the described architecture allows using one CNC system for different technological tasks using a laser without significant changes in the system architecture. The sequence of execution of the control program is described in detail for a fuller understanding of the principle of operation of the system.